Access to Justice through the Prism of Judicial Practice and Legal Theory - Shcherbanyuk, Oksana; Bzova, Laura (Teisė, 2023)
This article discusses the access to justice, perceived as a human right. It is argued that this fundamental right is now part of today’s jus cogens. The idea of jus cogens can be a highly beneficial tool for sanctifying the existence of a normative hierarchy in the international arena, which is traditionally viewed as a set of purely horizontal relations between states. As soon as a norm or a principle acquires the character of jus cogens, it obliges the entire international community, requiring states to adapt their laws and legal practice.
Keywords: access to justice; judicial authorities; court practice; jus cogens; judicial system